Evolution of anisotropic diffusion in the developing rat corpus callosum - Vorísek, I; Syková, E (Journal of neurophysiology, 1997)
Diffusion anisotropy was investigated in the developing rat brain [postnatal day (P)6-29] with the use of ion-selective microelectrodes to measure the three-dimensional distribution of tetramethylammonium (TMA+) iontophoresed into the extracellular space (ECS). The diffusion parameters, ECS volume fraction alpha (alpha = ECS volume/total tissue volume), tortuosity lambda (lambda2 = apparent diffusion coefficient/free diffusion coefficient), and nonspecific TMA+ uptake (k'), were studied in cortical gray matter (layer V) and corpus callosum (CC) of anesthetized rats. ECS volume fraction in cortex and CC was about twice as large in the newborn rat as in adults. In this study, more detailed analysis revealed that alpha in CC gradually decreased from P4, when alpha ranged between 0.42 and 0.45, and reached a final value of 0.26 +/- 0.01 (SE, n = 12 measurements, 6 animals) at about P21. Diffusion in the ECS of CC was isotropic until about P12, i.e., there was no significant difference in the tortuosity factor, lambda, between the three perpendicular axes. From P13 to P17 anisotropy greatly increased as a result of preferential diffusion along the myelinated axons (X-axis). At P21-23 the tortuosity values were lambda(x) = 1.46 +/- 0.03, lambda(y) = 1.70 +/- 0.01, and lambda(z) = 1.72 +/- 0.02 (n = 12), and there were no further changes up to the last postnatal day studied, P29. In contrast to the myelinated CC, cortical gray matter remained isotropic up to P29, with a tortuosity of 1.54 +/- 0.02 (n = 12). The results suggest that diffusion anisotropy in the rat CC is related to myelination; it reaches a maximum at P17, when myelination is well advanced. In myelinated pathways, preferential diffusion of ions and transmitters occurs along the axons. These results are relevant to volume transmission and the interpretation of diffusion-weighted magnetic resonance imaging.
Keywords: corpus callosum; Cerebral Cortex; Magnetic Resonance Imaging; gangliová stimulancia; kvartérní amoniové sloučeniny; difuze; zvířata; Anisotropy; magnetická rezonanční tomografie; Animals; anizotropie; krysa rodu Rattus; Ganglionic Stimulants; mozková kůra; Quaternary Ammonium Compounds; Rats; Rats, Wistar; Diffusion; potkani Wistar; Corpus Callosum